La incidencia Tributaria de las empresas de tabaco en la provincia de San Martín. Periodo 2009 - 2011 - Pérez Aguilar, Danilo (2013)
Main purpose in this thesis is to analyze the tax incidence on exporting companies snuff in the Province of San Martín. Period two thousand nine- two thousand and eleven, to determine if the tax regime is hosted each of the companies is the one that brings more economic benefits and demonstrate the accounting treatment performed in the same; onto the sample under study are three companies exporting snuff in the province of San Martín. The type of research according to the orientation was basic and according to the technique of contrasting was descriptive, for data collection used an interview script consists of twenty items (closed questions - open) and documentary art or literature. The validity of the same technique, using "expert judgment", expressing their opinions in order to revise its form and content. The results of this work show the tax benefits enjoyed by companies analyzed and customs procedures to which they are received, showing its impact positively established by standard and the contrast with reality. lt concludes that start a business exporting snuff foreign market is definitely an alternative to an entrepreneur from San Martín, Peru not only who is interested in their own economic development but also to generate more jobs and emblem to the region and because if not the country.